Measurements of the branching fraction ratio B(ϕ → μ+μ−)/B(ϕ → e+e−) with charm meson decays - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Cocha Toapaxi, Carlos; De Cian, Michel; Frau, Giulia; Glaser, Fabian; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Herrero Gascón, Paula; et al. (Journal of high energy physics, 2024)
Measurements of the branching fraction ratio B(ϕ → μ+μ−)/B(ϕ → e+e−) with D+s → π+ϕ and D+ → π+ϕ decays, denoted Rs ϕπ and Rd ϕπ, are presented. The analysis is performed using a dataset corresponding to an integrated luminosity of 5.4 fb−1 of pp collision data collected with the LHCb experiment. The branching fractions are normalised with respect to the B+ → K+J/ψ(→ e+e−) and B+ → K+J/ψ(→ μ+μ−) decay modes. The combination of the results yields Rϕπ = 1.022 ± 0.012 (stat) ± 0.048 (syst). The result is compatible with previous measurements of the ϕ → ℓ+ℓ− branching fractions and predictions based on the Standard Model.